Drug abuse in Syria: pattern of use, causes and perception as perceived by Syrian addicts. Issue 2 (21st February 2020) - Abazid, Husam; Abou‐Isba, Samir; Abu Farha, Rana; Al‐Jomaa, Esraa E.
Abstract: Objectives: We aimed to evaluate the current pattern, causes and attitude towards drug use amongst Syrian prisoners who were incarcerated due to their using drugs. Methods: This is a descriptive cross‐sectional survey‐based study that was conducted over a period of six months. Prisoners were recruited from two main civil prisons in Syria. The data collected in this study were through the use of a self‐administered survey. The prisoners were met in a separate room away from their dormitories and they were asked to fill out the survey after obtaining their verbal consent. Keyfindings: A total of 50 participants were recruited (response rate = 66.7%). Most of the prisoners ( n = 29, 58.0%) started to use drugs at a friend's home, and the most commonly used drug was Hashish (weed and cannabis) ( n = 22, 44.0%). Two‐thirds of the participants ( n = 34, 68.0%) said that they returned to drugs after quitting. The most common reason was using drugs for euphoria ( n = 12, 24.0%). Regarding prisoners' beliefs about different causes of drug use, curiosity was found to be the most common cause of drug use ( n = 19, 38.0%). Surprisingly, prisoners incorrectly believed that they can take drugs and they can stop them whenever they want ( n = 34, 68.0%) and that drug use does not lead to addiction ( n = 30, 60.0%). Conclusions: The findings of this study indicate the need to devote more attention to family and peer influences on an individual's behaviour by policymakers, in developing preventive strategies. As well as, the need to raise the awareness of individuals in the society about drug use, subsequently, changes their incorrect perceptions towards drugs through several strategies including educational programmes as well as workshops whether in school, universities or social media.